NUMERICAL STUDY OF COOLING BY TANGENTIAL SYNTHETIC JET - Munhoz, F.; Lee, C. Y. Y.; Alves, F. L. D. (Revista de Engenharia Térmica, 2015)
Modern electronics are becoming more compact and with higher processing power, which translates into a demand for higher heat dissipation. Current electronic "coolers," which are based on the combination of fans and heat sinks, are becoming unable to provide sufficient heat dissipation since they rely primarily on generating large volumetric flowrates of air to achieve their results. As an alternative, synthetic jets are under consideration due to their known property to enhance turbulence and heat transfer. Synthetic jets are produced by the oscillation of a membrane in a sealed cavity equipped with an orifice. For this study, a numerical model of channel mounted with a heating element on one surface and a synthetic jet directed to blow along the wall was constructed on ANSYS CFX. Heat dissipation provided by the synthetic jet was analyzed with respect to changes in Reynolds number, pulsing frequency and placement of the heated element. Results were compared to a conventional technique represented by a steady channel flow of equivalent mass flow rate to the average flow induced by the synthetic jet. Results showed that the synthetic jet formed a thin layer of intense vorticity along the targeted surface with cooling greatly outperforming conventional techniques. Synthetic jet cooling was also determined to be most affected by jet velocity and Reynolds number while pulsing frequency and placement of the heated element were not as influential.